Search for high mass dijet resonances with a new background prediction method in proton-proton collisions at √s = 13 TeV; Journal of High Energy Physics; Vol. 2020, iss. 5 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen